Коррозионное растрескивание хромоникелевых сталей в воде высоких параметров - Зубченко, А.С. (Автоматическая сварка, 2008)
The results of investigations of effect of oxygen and chlorine-ions on the susceptibility to corrosion cracking of chromium-nickel austenite steels in high- parameter water are given. For separate steels the results of tests in boiling water solutions containing 42 % MgCl₂ and 40 % CaCl₂ are given. The possibility for increase in service life of equipment and pipelines of reactor plants using austenite steels with high content of nickel and austenite-ferrite (duplex) steels due to their much higher resistance against corrosion cracking in cooling water media is shown.